The Impact of Stalking-Related Fear and Gender on Personal Safety Outcomes - Logan, TK (Journal of interpersonal violence, 2021)
Research has consistently found that more women worry about their personal safety and feel vulnerable to most every crime compared with men suggesting there is a gender fear gap. Environmental risk and prior victimization history impact concerns about personal safety. However, few studies include stalking as part of the victimization history. Two reasons studies may not include stalking are that adding more questions to a research assessment increases participant burden and measurement of stalking has not always been clear. The current study used a community sample of 2,719 men and women and a five-item stalking assessment to examine the prevalence and impact of stalking and stalking-related fear on concern about personal safety, perceived vulnerability to an attack, perceptions that risk of victimization is higher due to personal characteristics, discomfort when thinking about safety, and posttraumatic stress symptoms controlling for victimization history, age, and environment risk by gender. Overall, 30% of women and 12% of men experienced stalking using the extreme fear standard which is double the national rates. Stalking-related fear, for both women and men, was associated with all of the outcome measures. Furthermore, there were significant main effects of gender after controlling for stalking-related fear on three of the outcomes consistent with the gender fear gap. Based on these results, research studies should consider including stalking as part of the victimization history as it is likely to impact health and mental health outcomes as well as personal safety concerns and responses for both men and women.